Richard Byrd and his pet terrier "Igloo", 1928 - Unknown (University of Southern California Digital Library (USC.DL), 2012)
Richard Byrd and his pet terrier "Igloo", October 11, 1928.; With the South Pole conquered in 1911, the "heroic" age of Antarctic exploration ended. However, much of the interior remained to be discovered. In 1929 Richard Byrd reignited popular interest in the area when he made the first flight over the pole. Byrd established five successive bases in Antarctica (called Little Americas I-V) and led U.S. research on the continent until his death in 1957. His exploits were so well known that other countries raced south to set up permanent bases and claim portions of the land as their own.